Mortality in dementia is predicted by older age of onset and cognitive presentation. (July 2022) - Loi, Samantha M; Tsoukra, Paraskevi; Chen, Zhiben; Wibawa, Pierre; Mijuskovic, Tamara; Eratne, Dhamidhu; Di Biase, Maria A; Evans, Andrew; Farrand, Sarah; Kelso, Wendy; Goh, Anita MY; Walterfang, Mark; et al.
Objectives: Survival information in dementia is important for future planning and service provision. There have been limited Australian data investigating survival duration and risk factors associated with mortality in younger-onset dementia. Methods: This was a cross-sectional retrospective study investigating survival in inpatients with a diagnosis of dementia admitted to a tertiary neuropsychiatry service from 1991 to 2014. The Australian Institute of Health and Welfare National Death Index was used to obtain mortality information. Results: A total of 468 inpatients were identified, of which 75% had symptom onset at ⩽65 years of age (defined as younger-onset dementia). Dementia was categorised into four subtypes, Alzheimer's dementia, frontotemporal dementia, vascular dementia and other dementias; 72% of the patients had died. Overall median survival duration was 10.6 years with no significant differences in duration within the dementia subtypes ( p = 0.174). Survival in older-onset dementia (symptom onset at >65 years of age) was about half of that in younger-onset dementia (median survival 6.3 years compared to 12.7 years, respectively). Independent predictors of mortality were having older-onset dementia (hazard ratio: 3.2) and having initial presenting symptoms being cognitive in nature (hazard ratio: 1.5). Females with an older-onset dementia had longer survival compared to males with an older-onset dementia, and this was reversed for younger-onset dementia. Older-onset dementia and younger-onset dementia conferred 3 and 6 times, respectively, increased risk of death compared to the general population. Conclusion: This is the largest Australian study to date investigating survival and risk factors to mortality in dementia. We report important clinical information to patients with dementia and their families about prognosis which will assist with future planning. Our findings suggest that for both older-onset dementia and younger-onset dementia, 'new onset' psychiatric symptoms precede the cognitive symptoms of a neurodegenerative process. This, and sex differences in survival depending on the age of onset of the dementia warrant further investigation.